Seed dispersal effectiveness by a large-bodied invasive species in defaunated landscapes - Pedrosa, Felipe [UNESP]; Bercê, William [UNESP]; Levi, Taal; Pires, Mathias; Galetti, Mauro [UNESP] (Wiley, 2019)
Animal-dispersed plants are increasingly reliant on effective seed dispersal provided by small-bodied frugivores in defaunated habitats. In the Neotropical region, the non-native wild pig (Sus scrofa) is expanding its distribution and we hypothesized that they can be a surrogate for seed dispersal services lost by defaunation. We performed a thorough analysis of their interaction patterns, interaction frequencies, seed viability, and characteristics of the seed shadows they produce. We found 15,087 intact seeds in 56% of the stomachs and 5,186 intact seeds in 90% of the scats analyzed, 95% of which were smaller than 10 mm in diameter. Wild pigs were the third most effective disperser among 21 extant frugivore species in a feeding trail experiment in terms of quantity of seeds removed. Gut retention time was 70 ± 23 hr, indicating wild pigs can promote long-distance seed dispersal. Seed survival after seed handling and gut passage by wild pigs was positively related with seed size, but large seeds were spat out and only smaller seeds were defecated intact, for which we observed a positive or neutral effect on germination relative to manually de-pulped seeds. Finally, deposition of seeds was four times more frequent in unsuitable than suitable sites for seedling recruitment and establishment. Seed dispersal effectiveness by wild pigs is high in terms of the quantity of seeds dispersed but variable in terms of the quality of the service provided. Our study highlights that negative and positive effects delivered by non-native species should be examined in a case by case scenario. Abstract in Portuguese is available with online material.
Keywords: alien species; Anthropocene; Atlantic Forest; ecosystem services; feral pig; fragmentation; frugivory; Sus scrofa